Dynamic communication performance enhancement in Hierarchical Torus Network by selection algorithm - Rahman, M.M. Hafizur; Sato, Yukinori; Inoguchi, Yasushi (2010)
The static network performance and dynamic communication performance of the Hierarchical Torus Network (HTN) using dimension-order routing algorithm have already been evaluated and shown to be superior to the performance of other interconnection networks. However, the assessment of the dynamic communication performance improvement of HTN by the efficient use of both the physical link and virtual channels has not yet been evaluated. This paper addresses three adaptive routing algorithms - link-selection, channel-selection, and a combination of link-selection and channel-selection - for the efficient use of physical links and virtual channels of an HTN to enhance dynamic communication performance. It also proves that the proposed adaptive routing algorithms are deadlock-free with 3 virtual channels. The dynamic communication performances of an HTN is evaluated by using dimension-order routing and proposed adaptive routing algorithms under various traffic patterns. It is found that the dynamic communication performance of an HTN using these adaptive routing is better than when the dimension-order routing is used, in terms of network throughput.